Mitigating oscillator pulling due to magnetic coupling in monolithic mixed-signal radio-frequency integrated circuits - Sobering, Ian David (Kansas State University, 2014)
An analysis of frequency pulling in a varactor-tuned LC VCO under coupling from an on-chip PA is presented. The large-signal behavior of the VCO's inversion-mode MOS varactors is outlined, and the susceptibility of the VCO to frequency pulling from PA aggressor signals with various modulation schemes is discussed. We show that if the aggressor signal is aperiodic, band-limited, or amplitude-modulated, the varactor-tuned LC VCO will experience frequency pulling due to time-modulation of the varactor capacitance. However, if the aggressor signal has constant-envelope phase modulation, VCO pulling can be eliminated, even in the presence of coupling, through careful choice of VCO frequency and divider ratio. Additional mitigation strategies, including new inductor topologies and system-level architectural choices, are also examined. The analysis is then applied to improve a fully-integrated half-duplex UHF micro-transceiver in which signal coupling between the LO and PA caused frequency pulling that prevented the use of QPSK signaling at certain data rates. We determine that a VCO operating at 4x transmit frequency will be naturally insensitive to pulling from QPSK signals. To validate the proposed solution, a prototype IC containing a pair of QPSK transmitters with integrated 100mW Class-C PAs was designed and fabricated in 0.18um SOI. The transmitters--one utilizing a 2x VCO, one utilizing a 4x VCO-- were designed to closely match the performance of the original microtransceiver when transmitting QPSK data. The transmitter with the 2x VCO experienced frequency pulling from the PA while transmitting QPSK data, but the transmitter with the 4x VCO did not, thereby confirming the analysis in this work. A revision of the microtransceiver was designed in 0.5 [mu]m SOS utilizing an off-chip PA inductor to reduce signal coupling with the VCO. A second revision of themicrotransceiver with two prototype transmitters was designed in 0.25 [mu]m SOS utilizing 4x VCOs and figure-8 VCO inductors for maximum insensitivity to pulling from QPSK and band-limited modulation, as well as other design improvements that leverage the higher f[subscript]t of the smaller process. Both revisions also include a hardware FSK modulator, a new charge pump, and a redesigned fractional-N synthesizer to attenuate a divided-reference spur in the IF output. These revisions of the radio will enable future researchers to focus on system-level applications where highly-integrated medium-power transceivers with fully-functioning IQ modulation are needed.
Keywords: Pulling; Magnetic coupling; Silicon-on-insulator; Electrical Engineering (0544)